2015
DOI: 10.1111/hpb.12366
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management and classification of hepatic leiomyosarcoma

Abstract: Hepatic resection for leiomyosarcoma is associated with encouraging rates of 5-year overall and disease-free survival. The worse outcome that had been expected based on data derived from historical cohorts (partly comprising subjects with GIST) was not observed. An algorithm for pathological classification and treatment is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Only 2 patients, including the one reported in this study, developed single liver metastasis (5). Three cases, including the patient reported in our study, underwent surgery for liver metastasis (6), and 3 cases received chemotherapy for the metastatic lesions (5,7). There is no mention of surgical intervention or chemotherapy treatment for the secondary liver lesions in the remaining 3 cases.…”
Section: Discussionmentioning
confidence: 92%
“…Only 2 patients, including the one reported in this study, developed single liver metastasis (5). Three cases, including the patient reported in our study, underwent surgery for liver metastasis (6), and 3 cases received chemotherapy for the metastatic lesions (5,7). There is no mention of surgical intervention or chemotherapy treatment for the secondary liver lesions in the remaining 3 cases.…”
Section: Discussionmentioning
confidence: 92%
“…Potential origins of this tumor in the liver are the smooth muscle cells in the round ligament (29,31,37,38), the intrahepatic blood vessels and the intrahepatic bile ducts (15,17,22,26,29,31,32,37,38,40). There is no apparent sex predilection, since there have been reported 23 (46%) cases of male patients ( 25,27,28,31,36,[38][39][40]. The mean patients' age is 51.3 years and the median patients' age is 58 years.…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination of primary hepatic leiomyosarcomas shows spindle-shaped cells with fascicular arrangement (4, 8, 10-12, 15-17, 19, 21, 22, 26-34, 36-38, 40). Immunohistochemistry reveals expression of smooth muscle actin (13, 15, 18, 19, 21, 22, 27-33, 36-38, 40), desmin (13,15,19,21,22,(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38) and vimentin (15, 17, 19, 22, 27-29, 31, 33, 37, 38, 40), whereas cytokeratins (22, 27-33, 37, 38), neuron-specific enolase (27)(28)(29)32) and S-100 protein (19, 21, 27-34, 37, 38, 40) are not expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients also have palpable abdominal masses and unintentional weight loss [3,4,9]. Approximately 50% of patients will develop distant metastasis, most commonly to the liver, and lungs [3,9,11], and rarely to adjacent lymph nodes [7]; therefore, routine lymph node dissection is not recommended.…”
Section: Reviewmentioning
confidence: 99%
“…Hamed et al [11] n/a + n/a n/a + n/a n/a -Hamed et al [11] n/a + n/a n/a + n/a n/a -Dasgupta et al [18] n/a + n/a n/a + n/a n/a -Kato et al [5] n/a + n/a n/a + -n/a -Varghese et al [9] n/a + + n/a + n/a n/a n/a Ilias et al [6] n/a + + n/a + -+ -Dalal et al [1] n/a + n/a + + ---Schoucair et al [3] n/a + + n/a + n/a n/a n/a Yoon et al [14] n/a + n/a n/a + n/a n/a n/a Our reported case + + + + + -n/a n/a All patients were managed with surgical resection, apart from two cases where modality of treatment was not reported. The extent of resection was dependent on whether there is an invasion of adjacent structures.…”
Section: Referencesmentioning
confidence: 99%